The most important dilemmas regarding the welfare of farm animals - Hristov, Slavca; Stankovic, Branislav; Ostojic-Andric, Dusica; Maksimovic, Nevena; Nakov, Dimitar (National Library of Serbia, 2019)
In this review paper, contradictions in modern livestock production as dilemmas of farm animal welfare are considered. The main dilemma concerns the question of whether extensive production in small farms is generally better than intensive production in large farms. The next dilemma relates to an intensive selection of animals and its impact on the emergence of welfare problems. Another dilemma is related to the two main interconnected problems of pig welfare in individual farrowing pens: the piglet death by crushing and the sows’ movement restriction. Similarly, welfare dilemma is the paradox of parent flocks of broiler line breeding that could not be solved until the pressure for genetic advancement in production is required due to the economic efficiency. The next example of the dilemma is the widespread practice of tail docking in piglets in order to reduce the risk of tail biting. Although the tail docking is painful and may cause death, anaesthesia is usually not applied on farms. A similar example of the dilemma is debeaking in the laying hens and the occurrence of feather pecking in free rearing systems. It is important to notice the difference between the described dilemmas, where one premise opposes the other, which is essentially a conflict between the animal welfare goals and other values, such as economic, ethical and moral issues. Finally, there are also some dilemmas about the consumers’ willingness to pay a higher price of products that originate from welfare friendly rearing conditions.
Keywords: dilemma, welfare protection, farm animals